The Path to UVCB Ecological Risk Assessment: Grappling with Substance Characterization. (30th September 2022) - Salvito, Daniel; Fernandez, Marc; Arey, Jeremy S.; Lyon, Delina Y.; Lawson, Nelson; Deglin, Sandrine; MacLeod, Matthew
Abstract: Substances of unknown or variable composition, complex reaction products, and biological materials (UVCBs) pose a unique challenge to regulators and to product registrants, who are required to characterize their fate, exposure, hazard, and potential risks to human health and the environment. To address these challenges and ensure an efficient and fit‐for‐purpose process, it is proposed that the ecological risks of UVCBs be assessed following a tiered strategy. The development of this approach required exploring how substance composition ties into hazard and exposure information and determining the extent to which a UVCB needs to be characterized to ensure a robust risk assessment. The present study highlights the key aspects of this new method. It presents how a tiered substance characterization approach can be integrated into broader UVCB risk‐assessment schemes to encourage an examination of data needs before a full substance characterization is performed. The first tier of the characterization process, Tier 0, is a fundamental step that includes data from basic, lower‐resolution compositional analyses. Tier 0 assessments can be used to inform hazard and exposure for any substance of interest. The need for more sophisticated, higher‐tier characterization is determined by the level of uncertainty of the risk assessment. The next step will integrate a tiered exposure assessment into the characterization scheme featured in the present study, to create a more complete risk‐assessment framework. Environ Toxicol Chem 2022;41:2649–2657. © 2022 Her Majesty the Queen in Right of Canada, Health and Environmental Sciences Institute and The Authors. Environmental Toxicology and Chemistry published by Wiley Periodicals LLC on behalf of SETAC. Reproduced with the permission of the Minister of Environment and Climate Change Canada.